Pengalaman Pasien Diabetes dalam Menjalani Pola Hidup Sehat dan Dukungan Keluarga - Teuku Nabhan Zuhdi; Sri Nurhayati Selian (Observasi : Jurnal Publikasi Ilmu Psikologi, 2026)
Diabetes mellitus is a chronic disease with a steadily increasing prevalence in Indonesia. This condition not only affects physical health but also requires patients to make significant lifestyle changes to maintain stable blood glucose levels. Efforts to adopt a healthy lifestyle such as regulating diet, exercising regularly, and managing stress are often met with various challenges. In this context, family support plays a crucial role in helping patients adapt and remain consistent in self-management. This study aims to describe the experiences of type 2 diabetes patients in maintaining a healthy lifestyle and the forms of family support they receive. A qualitative phenomenological approach was used, involving three participants undergoing outpatient treatment at RSUD Sultan Iskandar Muda Nagan Raya. Data were collected through in-depth interviews, observations, and documentation, then analyzed thematically. The findings show that patients face challenges in maintaining dietary control, consistent exercise, and emotional balance. However, family support such as reminding patients to take medication, providing healthy meals, and offering emotional motivation serves as a key factor that strengthens patients’ commitment to a healthy lifestyle. The study concludes that the success of diabetes management is highly influenced by active family involvement. Therefore, educational and health intervention programs should integrate families as essential partners in supporting patients with diabetes.